Impact of Different Nitrogen Fertilizers on the Diversity and Abundance of Bacterial and Fungal Communities in Grassland Soils: The Emerging Case of Ammonium Sulfate and Sulfammox Process - Bella Tsachidou; Magdalena Calusinska; Christophe Hissler; Jérôme Gennen; Benjamin Daigneux; Séverine Piutti; Alexandre Laflotte; Isabelle George; Philippe Delfosse (GCB Bioenergy)
ABSTRACT Improving agricultural productivity to meet the growing food and feed demand via nitrogen fertilization comes with trade‐offs such as environmental pollution and biodiversity loss. Biogas residues (BRs) being a relatively new biofertilizer aiming at substituting chemical nitrogen fertilizers, have raised questions regarding their biosecurity and environmental footprint. In this study, we explored and compared the effect of repeated application of different nitrogen fertilizers on the bacterial and fungal α‐diversity, relative abundance, β‐diversity, and taxonomic composition in grassland soils over a period of two years. Given the paramount importance of arbuscular mycorrhizal fungi in sustainable agriculture and climate change, we examined the relative abundance of Glomeromycota and their response to the different nitrogen fertilizers. Finally, the soil microbial community was scanned for the most prominent pathogens that are often detected in BRs and are the main concern related to their application on agricultural soils. Microbial communities in the soil were identified and quantified via high‐throughput sequencing of the 16S rDNA marker gene for bacteria, and the ribosomal DNA Internal Transcribed Spacer (ITS2) region for fungi. Overall, the results suggest that the soil bacteriome is more sensitive than the mycobiome to nitrogen fertilization. Specifically, ammonium sulfate application appears to negatively impact bacterial alpha‐diversity, while also altering the relative abundance of Glomeromycota, prompting us to question the potential involvement of the sulfammox process in the loss of soil microbial diversity. Notably, the application of biogas residues did not alter the diversity or abundance of soil microbial communities, nor harbored any significant pathogens; therefore, advocating for their safety and encouraging further research to validate their safe nature and beneficial properties.